The turtle who danced with the crane - Cullimore, Stan.; Moxley, Sheila (England : Longman, 1998)
When Yim Sung, a hungry fisherman, catches a turtle in his net, he thinks that his bad luck has changed, and he will have lots to eat.But then he sees that the turtle is crying...